2020
DOI: 10.3390/cells9030556
|View full text |Cite
|
Sign up to set email alerts
|

Light-Mediated Control over TRPC3-Mediated NFAT Signaling

Abstract: Canonical transient receptor potential (TRPC) channels were identified as key players in maladaptive remodeling, with nuclear factor of activated T-cells (NFAT) transcription factors serving as downstream targets of TRPC-triggered Ca2+ entry in these pathological processes. Strikingly, the reconstitution of TRPC-NFAT signaling by heterologous expression yielded controversial results. Specifically, nuclear translocation of NFAT1 was found barely responsive to recombinant TRPC3, presumably based on the requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Thus, genetic modification of mast cells to overexpress TRPC6 or TRPC7 channels generated OptoBI-1 sensitivity that allows temporal sculpturing of Ca 2+ signals in these immune cells. Notably, membrane currents and cytosolic Ca 2+ levels did not decline synchronously upon fast, light-induced deactivation as previously reported for TRPC3 mutants in the HEK293 expression system (26). Remarkably long-lasting Ca 2+ elevations were triggered by repetitive TRPC6 activation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Thus, genetic modification of mast cells to overexpress TRPC6 or TRPC7 channels generated OptoBI-1 sensitivity that allows temporal sculpturing of Ca 2+ signals in these immune cells. Notably, membrane currents and cytosolic Ca 2+ levels did not decline synchronously upon fast, light-induced deactivation as previously reported for TRPC3 mutants in the HEK293 expression system (26). Remarkably long-lasting Ca 2+ elevations were triggered by repetitive TRPC6 activation.…”
Section: Discussionsupporting
confidence: 81%
“…Nonetheless, the coupling of TRPC activity to downstream effectors may be strictly dependent on their mode of activation (33). In a recent study, we were able to demonstrate the linkage of recombinant TRPC channels to the calcineurin (CaN)/NFAT pathway in HEK293 cells (26). Expression of a TRPC3 gain-offunction mutant displaying enhanced benzimidazole sensitivity, was found to enable control of NFAT activity by OptoBI-1 (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with others, our group found that TRPC3 exhibited ligand-dependent Ca 2+ selectivity. TRPC3 was found to have a carbachol (CCh)-induced P Ca /P Cs selectivity ratio of 3.7 [ 39 ], which was reduced when activated by a novel photoswitchable agonist OptoBI-1 (P Ca /P Cs = 3.06; [ 56 ]). Altogether, ligand-dependent Ca 2+ selectivity is likely a general feature of the TRP channel family, which might be subunit stoichiometry dependent, and should be considered as an important factor for governing signaling functions.…”
Section: The Trpc Pore Structure – Focus On Ca 2+ mentioning
confidence: 99%